The development of national entrustable professional activities to inform the training and assessment of public health and preventative medicine residents - Moloughney, Brent; Moore, Kieran; Dagnone, Damon; Strong, David (Canadian Medical Education Journal, 2017)
Background: Entrustable Professional Activities (EPAs) have emerged to bridge the gap between the learning of individual competencies and competence in real world practice. EPAs capture the critical core work of a discipline integrating competencies from multiple domains. This report describes the development of a set of EPAs for specialty training in Public Health and Preventive Medicine (PHPM) in Canada. Methods: The PHPM EPAs were developed using multiple existing sources. A combination of workshops and a national online survey was used to consult with PHPM program directors, the national specialty committee, and competency-based education experts. Results: A national survey of PHPM program directors had a 71% response rate with 80% or more of respondents agreeing with all of the 20 EPA titles and all but one of their descriptions. Competency developmental stage-specific milestones were identified for each EPA. Conclusion: The identification of the EPAs and their milestones will increase emphasis on the demonstrated performance of the specialty's core work. Simulations applicable to several EPAs have been developed. The EPAs have also been incorporated into a PHPM National Review Course and will be used to develop a national PHPM curriculum, as well as a national written practice examination.